(untitled) - Ravindran, Kannoo (New Jersey, 2014)
The Mathematics of Financial Models is an in-depth guide that helps readers break through common client financial problems and emerge with clearer strategies for solving issues in the future.
Keywords: Finance,Tài chính; Mathematical models,Mô hình toán học